Gender Perceptions of Religiusity and Machiavellian on Tax Evasion: an Empiric Study of Personal Taxpayers - Indah Masri (The International Journal of Business Review (The Jobs Review), 2022)
Tax evasion has long been a problem for governments around the world. This study examines the influence of religiosity, Machiavellian, and gender on tax evasion, as well as the role of gender in moderating the relationship between religiosity and Machiavellian on tax evasion. The sample of this research is 120 respondents who already have NPWP in Jakarta and surrounding areas. The study's results prove that religiosity has a positive effect on tax evasion, and Machiavellian has no effect on tax evasion. In contrast, gender has a significant negative effect on tax evasion. In addition, gender can moderate the relationship between religiosity against tax evasion, but gender cannot moderate the relationship between Machiavellian and tax evasion.